Counter-conduct and its Intra-modern Limits. Issue 2 (2nd April 2020) - Barrett, Jenny
ABSTRACT: This article critically explores the Foucauldian concept of "counter-conduct", which has recently been applied to the study of resistance in international relations (IR). Whilst a counter-conduct analytic can destabilise a power/resistance binary, I argue in this article that it does not fully overcome onto-political assumption. Drawing on postcolonial and decolonial perspectives, alongside discussions with protesters during the 2014 "Umbrella Movement" protests in Hong Kong, this article traces how a counter-conduct analytic can fix and flatten the politics and ethics of struggle in other ways. Specifically, I draw out three limiting assumptions about power/resistance articulated by Foucault, which are then implicated in a counter-conduct analytic: (1) his intra-modern critique of power; (2) his undivided reading of the subject; and (3) his valorisation of the politics of struggle. Offering a constructive critique, this article considers the stakes of unsettling these intra-modern limits and the consequences for an emerging counter-conduct research agenda.